Wafer-Scale Production of Uniform InAsyP1-y Nanowire Array on Silicon for Heterogeneous Integration - Shin, Jae Cheol; Lee, Ari; Mohseni, Parsian Katal; Kim, Do Yang; Yu, Lan; Kim, Jae Hun; Kim, Hyo Jin; Choi, Won Jun; Wasserman, Daniel; Choi, Kyoung Jin; Li, Xiuling (AMER CHEMICAL SOC, 2013)
One-dimensional crystal growth allows the epitaxial integration of compound semiconductors on silicon (Si), as the large lattice-mismatch strain arising from heterointerfaces can be laterally relieved. Here, we report the direct heteroepitaxial growth of a mixed anion ternary InAs(y)p(1-y) nanowire array across an entire 2 in. Si wafer with unprecedented spatial, structural, and special uniformity across the entire 2 in. wafer and dramatic improvements in aspect ratio (>100) and area density (>5 x 10(8)/cm(2)). Heterojunction solar cells consisting of n-type InAsyP1-y (y = 0.75) and p-type Si achieve a conversion efficiency of 3.6% under air mass 1.5 illumination. This work demonstrates the potential for large-scale production of these nanowires for heterogeneous integration of optoelectronic devices.
Keywords: SOLAR-CELLS; OPTICAL-PROPERTIES; INGAAS NANOWIRES; GROWTH; PERFORMANCE; GAAS; DENSITY